Modifikasi Teknis Yudisial Dalam Penyelesaian Sengketa Keputusan Fiktif Positif Sebagai Implikasi Berlakunya OMNIBUSLAW Cipta Kerja - Sulaiman, Mohammad Farouq (Universitas Widya Gama Malang, 2025)
Some of groups who interpret Article 175 number 7 paragraphs (4) and (5) of the Law on Job Creation (UU Ciptaker No. 6 of the year 2023), as a norm that eliminates the concept of positive fictitious decisions and eliminates the authority of the PTUN to adjudicate them, which is delegated to the relevant government agency. Through doctrinal research using an integral approach to the three underlying laws, an understanding of the existence of judicial technical modifications in resolving TUN disputes arising from positive fictitious decisions is obtained, namely through tiered procedures by taking administrative efforts in government agency first as mandatory. If it turns out that the appropriate solution has not been obtained, then the aggrieved community can take legal action as factual action lawsuit to the PTUN as a means and final option.